Effect of Pretreatment of Nanocomposite PES‐Fe3O4 Separator on Microbial Fuel Cells Performance. Issue 2 (18th November 2019) - Bavasso, Irene; Di Palma, Luca; Puglia, Debora; Luzi, Francesca; Dominici, Franco; Tirillò, Jacopo; Sarasini, Fabrizio; Torre, Luigi
Abstract : Nanocomposite membranes based on polyethersulfone (PES) and nanomagnetite have been investigated with regards to the effect of pretreatments on the electrochemical performance of microbial fuel cells (MFCs). Nanocomposite membranes containing various amounts of Fe3 O4 (5, 10, and 20 wt%) were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, thermogravimetric analysis, differential scanning calorimetry, and tensile tests. The application in MFC systems requires also chemical characterizations such as ion exchange capacity, water uptake, and oxygen permeability. The best formulation (PES10) showed electrochemical properties similar to the PES20. With the aim of obtaining a high‐performance membrane with a low filler dosage, a pretreatment procedure (1 h of boiling step in deionized water and 1 h of immersion in 0.5 M of H2 SO4 ) was adopted. The results of such pretreatment in terms of maximum power and current density were 10.59 ± 0.72 mW/m 2 and 52.07 ± 0.86 mA/m 2, respectively. The adoption of a pretreatment avoids the need of higher amount of nanofillers that can affect membrane surface roughness and its processing. Overall, the nanocomposite membranes represent a suitable technology in the MFC process. POLYM. ENG. SCI., 60: 371–379, 2019. © 2019 Society of Plastics Engineers